Study of Ozone (O3) Technology for Post-Harvest Handling of Horticultural Products - Sari, Indriati Meilina; Latuserimala, Gerald; Ansiska, Paisal (GEOFORUM, 2023)
It is important to recognize that horticultural products not only meet our nutritional needs but also support economic and ecological well-being. Beyond their nutritional aspects, horticultural products also have a positive impact on the environment. The planting of ornamental trees, flowers, and urban gardens helps absorb carbon dioxide, filter air pollution, and create habitats for wildlife. The spoilage of horticultural products is a complex and significant issue in the agricultural industry and food supply chain. In the context of global food security, food waste caused by the spoilage of horticultural products is a serious problem. The preservation of horticultural products using ozone technology is an innovative approach that has gained attention for extending shelf life, reducing damage from pathogenic microorganisms, and maintaining the quality and freshness of the products. This paper seeks the latest information on the use of ozone in the preservation of horticultural products and the challenges associated with it. The study employs a literature review method as the primary approach to data collection. Ozone (O3), a form of oxygen with strong oxidative properties, has proven to be highly effective in combating pathogenic microorganisms, eliminating unwanted odors, and extending the shelf life of horticultural products. However, despite its significant benefits, the use of ozone must be carried out with caution to avoid potential negative impacts on humans and the environment.